Digital Da'wah Studies: A Bibliometric Analysis of Trends, Patterns, and Collaboration Networks - Muhamad Dupi; Syamsi Mustofa Singgih Prayogo (Ushuluddin, Adab, and Dakwah Faculty of State Islamic University Ponorogo, 2025)
This study employs a bibliometric approach to analyze publication trends, research patterns, and collaboration networks in the field of digital da’wah (Islamic digital preaching) within Islamic studies. Using data extracted from the Dimensions database and visualized through VOSviewer, the research identifies significant developments in this domain. Findings reveal a marked increase in digital da’wah research in recent years, reflected by growing publication outputs and participation from diverse institutions and scholars worldwide. However, the analysis indicates limited collaborative networks among researchers, highlighting the need for stronger interdisciplinary and cross-regional partnerships. Key themes emerging from the literature include digital communication strategies, the role of social media in da’wah, and the opportunities and challenges of preaching in the digital era. This study maps the current landscape of digital da’wah research and suggests future directions, such as broader data coverage and deeper methodological exploration. The findings provide valuable insights for scholars and practitioners working at the dynamic intersection of Islamic propagation and evolving communication technologies. REFERENCES Abouzid, Mohamed, Anna K. Główka, and Marta Karaźniewicz-Łada. “Trend Research of Vitamin D Receptor: Bibliometric Analysis.” Health Informatics Journal 27, no. 4 (2021). https://doi.org/10.1177/14604582211043158. Akmaliah, Wahyudi, and Ibnu Nadzir. “The ‘Elective Affinity’ of Islamic Populism: A Case Study of Indonesian Politic Identity Within the Three Elections.” Studia Islamika 31, no. 1 (2024): 31–61. https://doi.org/10.36712/sdi.v31i1.36305. Chen, Yunqiang, Qing Wang, Hong Chen, Xiaoyu Song, Hui Tang, and Mengxiao Tian. “An Overview of Augmented Reality Technology.” Journal of Physics: Conference Series 1237, no. 2 (2019). https://doi.org/10.1088/1742-6596/1237/2/022082. Danaditya, Adya, Lynnette Hui Xian Ng, and Kathleen M. Carley. “From Curious Hashtags to Polarized Effect: Profiling Coordinated Actions in Indonesian Twitter Discourse.” Social Network Analysis and Mining 12, no. 1 (2022): 1–24. https://doi.org/10.1007/s13278-022-00936-2. Dewi, Pramita Sylvia, Ari Widodo, Diana Rochintaniawati, and Eka Cahya Prima. “Web-Based Inquiry in Science Learning: Bibliometric Analysis.” Indonesian Journal of Science and Mathematics Education 4, no. 2 (2021): 191–203. https://doi.org/10.24042/ijsme.v4i2.9576. Eck, Nees Jan van, and Ludo Waltman. “Citation-Based Clustering of Publications Using CitNetExplorer and VOSviewer.” Scientometrics 111, no. 2 (2017): 1053–70. https://doi.org/10.1007/s11192-017-2300-7. Eck, Nees Jan Waltman, Ludo. “Software Survey: VOSviewer, a Computer Program for Bibliometric Mapping.” Scientometrics 84, no. 2 (2010): 523–38. https://doi.org/10.1007/s11192-009-0146-3. Fu, Yuan Chih, Marcelo Marques, Yuen Hsien Tseng, Justin J.W. Powell, and David P. Baker. “An Evolving International Research Collaboration Network: Spatial and Thematic Developments in Co-Authored Higher Education Research, 1998–2018.” Scientometrics 127, no. 3 (2022): 1403–29. https://doi.org/10.1007/s11192-021-04200-w. Garfield, Eugene. “From the Science of Science to Scientometrics Visualizing the History of Science with HistCite Software.” Journal of Informetrics 3, no. 3 (2009): 173–79. https://doi.org/10.1016/j.joi.2009.03.009. Huang, Tianji, Weiyang Zhong, Chao Lu, Chunyang Zhang, Zhongqi Deng, Runtao Zhou, Zenghui Zhao, and Xiaoji Luo. “Visualized Analysis of Global Studies on Cervical Spondylosis Surgery: A Bibliometric Study Based on Web of Science Database and VOSviewer.” Indian Journal of Orthopaedics 56, no. 6 (2022): 996–1010. https://doi.org/10.1007/s43465-021-00581-5. Isetti, Giulia. “Online You Will Never Get the Same Experience, Never: Minority Perspectives on (Digital) Religious Practice and Embodiment during the COVID-19 Outbreak.” Religions 13, no. 4 (2022). https://doi.org/10.3390/rel13040286. Ismandianto, Ismandianto, Hasan Sazali, and Ahmad Tamrin Sikumbang. “Bibliometric Analysis of the Radio Da’wah Research.” Jurnal Dakwah Risalah 35, no. 1 (2024): 16. https://doi.org/10.24014/jdr.v35i1.28927. Karakus, Mehmet, Alpay Ersozlu, and Aaron C. Clark. “Augmented Reality Research in Education: A Bibliometric Study.” Eurasia Journal of Mathematics, Science and Technology Education 15, no. 10 (2019). https://doi.org/10.29333/ejmste/103904. Khakimova, A. Kh, O. V. Zolotarev, and M. A. Berberova. “Coronavirus Infection Study: Bibliometric Analysis of Publications on COVID-19 Using PubMed and Dimensions Databases.” Scientific Visualization 12, no. 5 (2021): 112–29. https://doi.org/10.26583/SV.12.5.10. Mansour, Nesrine. “The Holy Light of Cyberspace: Spiritual Experience in a Virtual Church.” Religions 13, no. 2 (2022). https://doi.org/https://doi.org/10.3390/rel13020121. Marín-Marín, José Antonio, Jesús López-Belmonte, Juan Miguel Fernández-Campoy, and José María Romero-Rodríguez. “Big Data in Education. A Bibliometric Review.” Social Sciences 8, no. 8 (2019). https://doi.org/10.3390/socsci8080223. Mishol-Shauli, Nakhi, and Oren Golan. “Smartphone Religious Networking: Negotiating Contested Identities within a Pious Community over WhatsApp.” Religions 13, no. 11 (2022). https://doi.org/10.3390/rel13111034. Mukherjee, Debmalya, Satish Kumar, Naveen Donthu, and Nitesh Pandey. 2006 to 2020 : A Bibliometric Analysis and Future Directions. Management International Review. Vol. 61, 2021. https://doi.org/10.1007/s11575-021-00454-x. Naggar, Shaimaa El. “The Impact of Digitization on the Religious Sphere: Televangelism as an Example.” Indonesian Journal of Islam and Muslim Societies 4, no. 2 (2014): 189–211. https://doi.org/10.18326/ijims.v4i2.189-211. Novak, Christoph, Miriam Haselbacher, Astrid Mattes, and Katharina Limacher. “Religious ‘Bubbles’ in a Superdiverse Digital Landscape? Research with Religious Youth on Instagram.” Religions, 2022. https://doi.org/https://doi.org/10.3390/rel13030213. Oyewola, David Opeoluwa, and Emmanuel Gbenga Dada. “Exploring Machine Learning: A Scientometrics Approach Using Bibliometrix and VOSviewer.” SN Applied Sciences 4, no. 5 (2022). https://doi.org/10.1007/s42452-022-05027-7. Phoong, Seuk Yen, Shi Ling Khek, and Seuk Wai Phoong. “The Bibliometric Analysis on Finite Mixture Model.” SAGE Open 12, no. 2 (2022). https://doi.org/10.1177/21582440221101039. Rusydiana, Aam S., Muhamad Taqi, Irman Firmansyah, Aisyah Assalafiyah, and Nanik Kustiningsih. “A Bibliometric Analysis of Islamic Accounting Research Indexed by Dimensions.Ai.” Library Philosophy and Practice 2020, no. January (2020): 1–15. https://digitalcommons.unl.edu/libphilprac/4803. Santosa, Eka Budhi, Baskoro Hadi, Singgih Subiyantoro, Oka Irmade, and Fatma Sukmawati. “Augmented Reality for Student Learning Media: A Bibliometric Analysis and Visualization.” Indonesian Journal of Instructional Media and Model 3, no. 2 (2021): 47. https://doi.org/10.32585/ijimm.v3i2.2007. Shah, Syed Hamad Hassan, Shen Lei, Muhammad Ali, Dmitrii Doronin, and Syed Talib Hussain. “Prosumption: Bibliometric Analysis Using HistCite and VOSviewer.” Kybernetes 49, no. 3 (2020): 1020–45. https://doi.org/10.1108/K-12-2018-0696. Sovacool, Benjamin K., Chux Daniels, and Abbas AbdulRafiu. “Science for Whom? Examining the Data Quality, Themes, and Trends in 30 Years of Public Funding for Global Climate Change and Energy Research.” Energy Research and Social Science 89, no. March (2022): 102645. https://doi.org/10.1016/j.erss.2022.102645. Törnberg, Anton, and Petter Törnberg. “Author ’ s Accepted Manuscript Topic Modeling and Critical Discourse Analysis.” Discourse, Context and Media, 2016. http://dx.doi.org/10.1016/j.dcm.2016.04.003. Wahid, Soleh Hasan. “Exploring the Intersection of Islam and Digital Technology: A Bibliometric Analysis.” Social Sciences and Humanities Open 10, no. August (2024): 101085. https://doi.org/10.1016/j.ssaho.2024.101085. Zupic, Ivan, and Tomaž Čater. “Bibliometric Methods in Management and Organization.” Organizational Research Methods 18, no. 3 (2015): 429–72. https://doi.org/10.1177/1094428114562629. Zyoud, S. H., W. S. Waring, S. W. Al-Jabi, and W. M. Sweileh. “Global Research Production in Glyphosate Intoxication from 1978 to 2015: A Bibliometric Analysis.” Human and Experimental Toxicology 36, no. 10 (2017): 997–1006. https://doi.org/10.1177/0960327116678299. Zyoud, Sa’ed H., Muna Shakhshir, Amer Koni, Moyad Shahwan, Ammar A. Jairoun, and Samah W. Al-Jabi. “Olfactory and Gustatory Dysfunction in COVID-19: A Global Bibliometric and Visualized Analysis.” Annals of Otology, Rhinology and Laryngology 132, no. 2 (2023): 164–72. https://doi.org/10.1177/00034894221082735.